(untitled) (Jurnal EurekaMatika, 2017)
Volume of vehicles coming into the city of Bandung through toll gates in the city of Bandung is the seasonal multivariate time series data. To obtain a prediction volume of vehicles that go through the toll booths in the future requires a forecasting model. One of model multivariate time series that connects between the time and the location, where the data of the time series data is seasonally namely Vector Autoregressive-Generalized Space Time Autoregressive (VAR-GSTAR)models. This model has two orders, the order of the time obtained from the VAR model and order the space obtained from GSTAR. connection between the space on this model is indicated by the weighting of the location. This research used a weight normalized cross correlation. Forecast results obtained from the VAR-GSTAR model on the data volume of vehicles coming into the city of Bandung through toll gates in the city of Bandung is to follow the pattern of previous data, which fluctuates with rising tendency. ABSTRAK Data volume kendaraan yang masuk ke Kota Bandung melalui gerbang tol yang berada di Kota Bandung adalah data runtun waktu multivariate berpola musiman. Untuk memperoleh prediksi volume kendaraan yang masuk melalui gerbang tol dimasa yang akan datang dibutuhkan suatu model peramalan. Salah satu model runtun waktu multivariat yang menghubungkan keterkaitan antara waktu dan lokasi, dimana data runtun waktu tersebut berpola musiman adalah model Vector Autoregressive-Generalized Space Time Autoregressive (VAR-GSTAR). Model ini terdiri dari 2 orde yaitu orde waktu yang diperoleh dari model VAR dan orde spasial yang diperoleh dari model GSTAR. Keterkaitan antar ruang pada model ini ditunjukkan dengan pembobotan lokasi. Dalam penelitian ini digunakan bobot lokasi normalisasi korelasi silang. Hasil ramalan yang diperoleh dari model VAR-GSTAR pada data volume kendaraan yang masuk ke Kota Bandung melalui gerbang tol yang berada di Kota Bandung adalah mengikuti pola data yang sebelumnya, yaitu berfluktuasi dengan kecenderungan yang naik.